Improving Veteran Access to Integrated Management of Back Pain (AIM-Back): Protocol for an Embedded Pragmatic Cluster-Randomized Trial. (10th December 2020) - George, Steven Z; Coffman, Cynthia J; Allen, Kelli D; Lentz, Trevor A; Choate, Ashley; Goode, Adam P; Simon, Corey B; Grubber, Janet M; King, Heather; Cook, Chad E; Keefe, Francis J; Ballengee, Lindsay A; et al.
Abstract: Background: Coordinated efforts between the National Institutes of Health, the Department of Defense, and the Department of Veterans Affairs have built the capacity for large-scale clinical research investigating the effectiveness of nonpharmacologic pain treatments. This is an encouraging development; however, what constitutes best practice for nonpharmacologic management of low back pain (LBP) is largely unknown. Design: The Improving Veteran Access to Integrated Management of Back Pain (AIM-Back) trial is an embedded pragmatic cluster-randomized trial that will examine the effectiveness of two different care pathways for LBP. Sixteen primary care clinics will be randomized 1:1 to receive training in delivery of 1) an integrated sequenced-care pathway or 2) a coordinated pain navigator pathway. Primary outcomes are pain interference and physical function (Patient-Reported Outcomes Measurement Information System Short Form [PROMIS-SF]) collected in the electronic health record at 3 months (n=1, 680). A subset of veteran participants (n=848) have consented to complete additional surveys at baseline and at 3, 6, and 12 months for supplementary pain and other measures. Summary: AIM-Back care pathways will be tested for effectiveness, and treatment heterogeneity will be investigated to identify which veterans may respond best to a given pathway. Health care utilization patterns (including opioid use) will also be compared between care pathways. Therefore, the AIM-Back trial will provide important information that can inform the future delivery of nonpharmacologic treatment of LBP.